Crescimento pró-pobre e educação do Nordeste - Barbosa, Rafael Barros (2011)
This work aims to analyze the impact of education, measured as average years of schooling mean, and educational inequality on poverty reduction and promotion of economic growth to Northeast states in the period 1995-2008. In order to meet these objectives, three econometric models are applied: 1) a panel model such that income of poor is the dependent variable; 2)a multinomial model with panel data that used Kakwani-Pernia index as dependent variable and 3) an ordered multinomial model, considering three earning thresholds for indigents, poors and nonpoors based upon poverty lines. According to PNAD data, excepting the Census of 2000, the results allow to conclude that: i) average schooling plays an important role to explain the pro-poor growth in Northeast, ii) educational inequality has a substantial impact on poverty reduction and pro-poor growth.